Analiza metod identyfikacji elektronicznej stosowanych w Polsce - Lewandowski, Remigiusz (Wydawnictwo Uniwersytetu Wrocławskiego. Wydawnictwo "Szermierz" sp. z o.o., 2023)
The article is based on the analysis of technological solutions used in Poland in the field of electronic (remote) identification. These solutions were analyzed in terms of various criteria, including: adequacy to individual stages of the identification process as well as various types of functionalities and features, such as scope of used data, scope of applications, requirements for service providers, as well as expected compliance with eIDAS2. The article leads to the conclusion that Poland has very developed and widely used solutions in the field of electronic identification. In principle, they may be grouped into tools used to issue means of electronic identification and tools used in authentication as well as authorisation stages. Moreover, a significant part of the analyzed tools are applicable both in the public and commercial channels. Among all the solutions constituting the subject of this research, the greatest social utility from the point of view of security and public accessibility is ensured by: bank identity solutions and video verification based on the electronic layer of the ID card.
Keywords: eIDAS2; identity; identification; means of electronic identification